Establishment of seat pitch and seat tray table’s height as significant factors for aircraft passengers’ flight comfort through triangulation method - Salim, Salim Mkubwa; Romli, Fairuz Izzuddin; Harmin, Mohammad Yazdi; Mazlan, Norkhairunnisa; Abang Abdul Majid, Dayang Laila (The Aeronautical and Astronautical Society of the Republic of China, 2025)
In-flight comfort has become one of the main considerations for aircraft passengers in choosing their air travel options. It is therefore imperative for airlines to be able to provide a good flying cabin comfort to their passengers throughout the flight in order to be more competitive in the air transportation market. As indicated in several previous studies, one of the primary aspects of in-flight comfort can be related to the ease of passengers in performing inflight activities while being seated. It is believed that the passengers’ comfort during the in-flight activities is highly affected by the seat pitch and the height of seat tray table. To establish the influence of these two factors on aircraft passengers’ comfort while performing their in-flight activities, triangulation approach is applied in this study. Three different data collection methods are conducted, which are online survey, focus group session and group discussion conducted at aircraft cabin mock-up. The collected data is then triangulated to reach the conclusion on effects of height of seat tray table and seat pitch to aircraft passengers’ comfort during in-flight activities. All in all, results of the data triangulation indicate that current aircraft cabin is not comfortable for all aircraft passengers, particularly for them to do their typical in-flight activities. The ease and comfort to perform in-flight activities has been noted as crucial for aircraft passengers and this affects their overall flying comfort. Both seat pitch and height of seat tray table have been cited as influential factors that affect the comfort and ease of passengers in doing in-flight activities.